Potential of Malaria Vaccine in Eliminating Malaria: a Systematic Literature Review - Mofu, Renold M.; Mulyani, Wiwiek; Purba, Lilys Irianty Natalia (Poltekkes Kemenkes Palu, 2024)
Introduction: Malaria vaccines show significant potential for disease control but face challenges, including declining efficacy over time and resistance to drugs and insecticides. Despite the initial success of vaccines like RTS,S/AS01, an integrated approach is still needed to address malaria’s complex transmission dynamics across endemic regions. This review examines the current status, challenges, and future prospects of malaria vaccine development, focusing on the impact of combining pre-erythrocytic vaccines and transmission-blocking drugs using mathematical modeling to enhance their effectiveness in reducing transmission. Methods: A systematic literature review was conducted using the PICO framework to evaluate the effectiveness of malaria vaccines in reducing disease transmission. The review included studies involving vulnerable populations, particularly children in African countries. It compared the effectiveness of malaria vaccines with other control strategies, such as insecticide-treated bed nets and antimalarial drugs. Five relevant primary journals were analyzed using databases like PubMed, Scopus, and Google Scholar. Results: Findings reveal that newly developed malaria vaccines have significant potential to reduce malaria cases. However, large-scale implementation and regular vaccination strategies are required for sustained effectiveness. Genetic studies highlight the emergence of resistance, emphasizing the need for adaptable vaccines and strategies. Conclusion: Malaria vaccines, while promising, face obstacles such as waning efficacy and resistance. A combined strategy involving vaccines and transmission-blocking treatments is essential for global malaria elimination. Further research and strategic implementation are needed to optimize vaccine effectiveness and overcome these challenges.